PENGARUH MODEL PEMBELAJARAN PEER TEACHING TERHADAP KEMAMPUAN TEKNIK DASAR PERMAINAN BOLA BASKET PADA SISWA KELAS X SMK MUHAMMADIYAH 2 CIKAMPEK - Zulkarnain Haq; Rahmat Iqbal; Dhika Bayu Mahardhika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the peer teaching model on improving basic basketball skills among tenth-grade students at SMK Muhammadiyah 2 Cikampek. The main problem addressed in this research is the low level of students’ basic basketball skills due to teacher-centered learning methods. This study employed a quantitative approach with a quasi-experimental design, specifically the pretest-posttest control group design. The research sample consisted of 60 students, divided into experimental and control groups using the purposive sampling technique. The research instrument was a basic basketball skills test (dribbling, passing, and shooting) that had been tested for validity and reliability. Data were analyzed using an independent t-test with the help of SPSS version 26 at a significance level of 0.05. The results showed a significant difference between the experimental and control groups, with a t-value of 6.12 > t-table 2.00 and p = 0.000 < 0.05. This indicates that the implementation of the peer teaching model has a significant effect on improving students’ basic basketball skills. The experimental group demonstrated a higher average score improvement than the control group. In conclusion, the peer teaching model is effective in enhancing students’ basic basketball skills through collaborative learning among peers. Practically, these findings can serve as a reference for physical education teachers to apply teaching methods that foster active participation, cooperation, and student responsibility. Theoretically, this study strengthens the relevance of social learning theory in the context of physical education in vocational schools.